2020
DOI: 10.6007/ijarbss/v10-i9/7718
|View full text |Cite
|
Sign up to set email alerts
|

Financial Sector Policies and Economic Growth: Evidence From Insurance Sector in Nigeria

Abstract: This study investigated the financial sector policies and economic growth link in Nigeria with a focus more on the insurance sub-sector. The study adopted the time series research design, where data for evaluation covering the period 2010 to 2018 were obtained from several editions of the Central Bank of Nigeria (CBN) Statistical Bulletin. Gross capital formation, total insurance premium and total insurance investment were used to represent financial sector policies, while gross domestic product was used as pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Economic growth, according to Ogunlokun and Adeleke [7], is a process in which an economy's drivers improve through time, resulting in an increase in national income levels. Hence, in this study, economic growth is one of the variables to be measured and the study agrees with the foregoing submission of Etale and Edoumiekumo [13] and measures economic growth using real Gross Domestic Product of Nigerian Economy as this is the most popular metric of economic growth found in the literature.…”
Section: Economic Growthsupporting
confidence: 84%
See 3 more Smart Citations
“…Economic growth, according to Ogunlokun and Adeleke [7], is a process in which an economy's drivers improve through time, resulting in an increase in national income levels. Hence, in this study, economic growth is one of the variables to be measured and the study agrees with the foregoing submission of Etale and Edoumiekumo [13] and measures economic growth using real Gross Domestic Product of Nigerian Economy as this is the most popular metric of economic growth found in the literature.…”
Section: Economic Growthsupporting
confidence: 84%
“…Insurance, according to Etale and Edoumiekumo [13], is the business of guiding against the risk of unknowns and minimizing the risk for the both insured party and third parties. Insurance is a business that protects individuals and businesses against the occurrence of an uncertain event in the future.…”
Section: Insurancementioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, GCF and total insurance premium presented insignificant negative effect on GDP, while the total insurance investment had positive relationship to GDP. The study concluded that financial sector policies demonstrated statistically significant contribution to economic growth with a coefficient of determination and probability of F-statistics values of 0.99246 and 0.00001 0.05 levels of significance respectively [6].…”
Section: Empirical Reviewmentioning
confidence: 94%